Knowledge, attitudes, and practices of dentists about patients with HIV/AIDS: a descriptive study at the dentists - Pasaribu Saruksuk, Astri Suryani; Hasibuan, Sukri Paramita; Hayati, Fitrah; Nasution, Elisa Widyasari; Siregar, Darmayanti; Yanti, Gema Nazri (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Human Immunodeficiency Virus (HIV) is still an alarming global public health problem. Individuals infected with HIV can develop Acquired Immune Deficiency Syndrome (AIDS) when the infection reaches an advanced stage. Dentists are a group at high risk of contracting HIV/AIDS. Therefore, dentists must have good knowledge, attitudes, and practices towards HIV/AIDS patients. The purpose of this study was to determine the knowledge level, attitudes, and practices of dentists about patients with HIV/AIDS. Method: This type of research was descriptive with a cross-sectional design and was carried out directly at dentists' private practices or clinics in Medan. A total of 1319 dentists in Medan included 299 dentists during 2024 using a simple random sampling method. Data collection regarding knowledge, attitudes, and practices towards patients with HIV/AIDS from dentists in Medan was carried out using questionnaires. Results: The majority of respondents had a better level of knowledge regarding HIV/AIDS at 51.2%, followed by 44.5% of respondents having a moderate level of knowledge and only 4.3% of respondents having a poor level of knowledge. The majority of respondents had a neutral attitude, namely 58.9% and 34.8% of respondents had a negative attitude, and only 6.4% of respondents had a positive attitude towards patients with HIV/AIDS. The majority of respondents had a good level of practice at 49.2%, 44.1% of respondents had a moderate level of practice, and only 6.7% of respondents had a poor level of practice towards patients with HIV/AIDS. Conclusion: Satisfactory level of knowledge, neutral attitudes, and good practices regarding patients with HIV/AIDS. To maintain a good level of knowledge and practice and establish positive attitudes towards patients with HIV/AIDS, there is a need for improvement in education and post-graduate courses, refresher courses, seminars, and training about HIV/AIDS.KEYWORDSknowledge, attitudes, practices, HIV/AIDS, dentists